Auriculotherapy for anxiety, quality of life and fear of COVID-19 in pregnant women: a randomized clinical trial - Hérica Pinheiro Corrêa; Kauê Batista Andrade; Tânia Couto Machado Chianca; Antônio Prates Caldeira; Carolina Amaral Oliveira Rodrigues; Maria Fernanda Santos Figueiredo Brito; Caroline de Castro Moura; Diego Dias de Araújo (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to assess the effect of auriculotherapy on anxiety, quality of life and fear of COVID-19 in pregnant women. Methods: multicenter, single-blind, randomized clinical trial. Fifty-three pregnant women participated in intervention group and 51 in placebo group. Outcomes were measured by State Anxiety Inventory, World Health Organization Quality of Life-Bref, Fear of COVID-19 Scale and intervention assessment. Data were analyzed using Generalized Estimating Equations. Results: in both groups, there was reduced anxiety. In terms of quality of life, intervention group showed significant improvement in physical and environmental domains. In psychological domain, there was improvement in both groups, and in social domain, there was no significant change. Fear of COVID-19 decreased significantly in both groups. Conclusions: auriculotherapy had an effect equal to that of the placebo group in reducing anxiety and fear of COVID-19, and superior effect in the quality of life physical and environmental domains. REBEC: RBR-7fsjmyc.